Reduced Order Observer Based Synchronization and Secure Communication for a Class of Nonlinear Chaotic Systems - Ranjan, Ravi Kumar; Sharma, B.B. (Journal of Applied Nonlinear Dynamics, 2026)
The present work addresses simplistic approach of synchronization strategy for a class of nonlinear chaotic systems with reduced order observer in master-slave configuration. To establish synchronization objective, the system state dynamics is decoupled into dynamics of measurable and unmeasurable states to obtain the estimation error dynamics. Lyapunov stability criterion based observer stabilizes the estimation error which implies synchronization. Reduced order observer design scheme utilizes only the measurable states of master system for estimation. Even to tackle case of multiple states nonlinearity, only output states of system is required which makes it simpler and economical for practical controllers applications. Moreover, to avoid dependence of reduced order observer on derivative of output state dynamics, suitable coordinate transformation is proposed. For real-time applicability, synchronization effectiveness is utilized for secure chaotic communication using n-cipher encryption-decryption methodology. The derived scheme of synchronization and secure communication is also validated in presence of external random noise but its scope can be extended to class of nonlinear systems as well. For numerical simulations, detailed results for chaotic Lorenz system belonging to addressed class are presented.